Relation between proteome characterization and semen quality in Italian chicken breeds - Simona Nonnis; Elisa Maffioli; Joshua Grana; Manuela Madeddu; Luisa Zaniboni; Stefano Paolo Marelli; Vera Perricone; Nicolaia Iaffaldano; Gabriella Tedeschi; Silvia Cerolini (PLoS ONE, 2025)
The conservation of local chicken breeds is essential to safeguard genetic biodiversity and promote sustainable poultry production. Sperm cryopreservation is a key tool for the long-term maintenance of genetic diversity by enabling the storage of male gametes from endangered or valuable breeders for future use in conservation and breeding programs. However, significant variability in semen quality and fertility across breeds limits the effectiveness of cryopreservation protocols. This study aimed to explore the relationship between sperm protein composition and semen quality in five Italian chicken breeds, Bionda Piemontese (BP), Bianca di Saluzzo (BS), Mericanel della Brianza (MB), Pepoi (Pe), and Robusta Maculata (R), known for distinct reproductive traits. Semen samples were analyzed for volume, concentration, membrane integrity, and sperm motility, and for sperm proteomes by a label-free shotgun proteomics approach, to characterize potential molecular pathways associated with semen quality. Significant inter-breed differences were observed in semen parameters; Pe roosters showed the highest semen volume and concentration, but lower values in kinematic traits, including curvilinear velocity (VCL), straight-line velocity (VSL), and average path velocity (VAP). RM and MB exhibited the most favorable sperm membrane integrity, progressive sperm motility and sperm kinematic profile, with high VCL, VSL, VAP, linearity and wobble, despite lower semen volume. The remaining breeds showed intermediate values across most traits. Overall, results suggest breed-specific patterns and a potential trade-off between semen quantity and sperm motion efficiency. Proteomic analysis showed that proteins involved in energy metabolism, cytoskeletal dynamics, and membrane integrity were differentially abundant across breeds and correlated with specific semen traits. Gene Set Enrichment Analysis revealed enrichment of pathways such as the HSP90 chaperone cycle, TP53 transcriptional regulation, and insulin-like growth factor signaling in association with sperm motility and quality. Our findings demonstrate that sperm proteomes are associated with breed-specific fertility traits. This study provides new insights into the molecular basis of semen quality variability and biological conservation of avian genetic resources.